EFEKTIVITAS MEDIASI SEBAGAI UPAYA PENYELESAIAN PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA (STUDI PADA CV. ANUGRAH JAYA KAB. BANGKALAN) - Ana Sokhifatul Mufida; Meike Rizki Damayanti; Reda Prastyo (Universitas Trunojoyo Madura, 2018)
ABSTRACTThis article discusses about the effectiveness of mediation as conflict completion effort of the termination of employment.This article aims to know the effectiveness of mediation as conflict completion effort of the termination at CV. Anugrah Jaya Bangkalan. This type of research uses analytical descriptive, in order to describe and analyze disputes that occur at CV. Anugrah Jaya Indicators of the dispute are one of the workers named Ika Oktaviani who has embezzled the company's money. From the results of the study can be concluded, mediation as an effort to resolve disputes on termination of employment at CV. Anugrah Jaya works effectively. Mediation is carried out at the Department Of Industry and Labor Bangkalan, where the role of the mediator is very much needed until finally there is a decision that Ika Oktaviani was laid off by CV. Anugrah Jaya.